Water for agriculture: Maintaining food security under growing scarcity - Rosegrant, Mark W.; Ringler, Claudia; Zhu, Tingju (Annual Reviews, 2009)
Irrigated agriculture is the main source of water withdrawals, accounting for around 70% of all the world's freshwater withdrawals. The development of irrigated agriculture has boosted agricultural yields and contributed to price stability, making it possible to feed the world's growing population. Rapidly increasing nonagricultural demands for water, changing food preferences, global climate change, and new demands for biofuel production place increasing pressure on scarce water resources. Challenges of growing water scarcity for agriculture are heightened by the increasing costs of developing new water, soil degradation, groundwater depletion, increasing water pollution, the degradation of water-related ecosystems, and wasteful use of already developed water supplies. This article discusses the role of water for agriculture and food security, the challenges facing irrigated agriculture, and the range of policies, institutions, and investments needed to secure adequate access to water for food today and in the future.